Peptide–Drug Conjugates as Next-Generation Therapeutics: Exploring the Potential and Clinical Progress - Krishna Jadhav; Ashwin Abhang; Eknath B. Kole; Dipak Gadade; Apurva Dusane; Aditya Iyer; Ankur Sharma; Saroj Kumar Rout; Amol D. Gholap; Jitendra Naik; Rahul K. Verma; Satish Rojekar (Bioengineering)
Peptide–drug conjugates (PDCs) have emerged as a next-generation therapeutic platform, combining the target specificity of peptides with the pharmacological potency of small-molecule drugs. As an evolution beyond antibody–drug conjugates (ADCs), PDCs offer distinct advantages, including enhanced cellular permeability, improved drug selectivity, and versatile design flexibility. This review provides a comprehensive analysis of the fundamental components of PDCs, including homing peptide selection, linker engineering, and payload optimization, alongside strategies to address their inherent challenges, such as stability, bioactivity, and clinical translation barriers. Therapeutic applications of PDCs span oncology, infectious diseases, metabolic disorders, and emerging areas like COVID-19, with several conjugates advancing in clinical trials and achieving regulatory milestones. Innovations, including bicyclic peptides, supramolecular architectures, and novel linker technologies, are explored as promising avenues to enhance PDC design. Additionally, this review examines the clinical trajectory of PDCs, emphasizing their therapeutic potential and highlighting ongoing trials that exemplify their efficacy. By addressing limitations and leveraging emerging advancements, PDCs hold immense promise as targeted therapeutics capable of addressing complex disease states and driving progress in precision medicine.